Pengaruh Teman Sebaya dan Penerapan Tata Tertib Sekolah terhadap Kedisiplinan Belajar Siswa Kelas XI Tahun Ajaran 2024/2025 di SMA Negeri 1 Sunggal - Dahsyat Obrien L. Tobing, Samuel; Yuni, Revita (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to determine the influence of peers and the implementation of school rules on student learning discipline in grade XI students at SMA Negeri 1 Sunggal. This study uses a quantitative approach with an associative method. The research sample was 99 grade XI students taken through random sampling techniques. The instrument used was a questionnaire that had been tested for validity and reliability. The data analysis technique used was multiple linear regression. The results of the study showed that peers have a positive and significant effect on students' learning discipline with a t-value of 7.248>t table 1.660 and a significance of 0.000<0.05. The regression coefficient of 0.444 indicates that the higher the student's peer interaction, the higher the student's learning discipline. The implementation of school rules also has a positive and significant effect with a t-value of 2.613>t table 1.660 and a significance of 0.010<0.05 and a regression coefficient of 0.188. Simultaneously, both variables have a significant effect on students' learning discipline, as evidenced by the F-value of 32.387>F table 3.09 and a significance value of 0.000<0.05. The R² value of 0.403 indicates that 40.3% of the variation in students' learning discipline can be explained by peers and the implementation of school rules. This finding confirms the importance of the role of peers around students and the encouragement of implementing school rules in determining the level of student learning discipline